Implementasi Arsitektur Publish/Subscribe pada Sistem Hidroponik menggunakan NodeMCU V3 - Siswanto, Diky; Olga Tahitya, Candrasa; Priyandoko, Gigih (Jurnal FORTECH, 2025)
The agricultural sector plays a vital role in national food security; however, land scarcity due to rapid urbanization has encouraged the adoption of alternative methods such as hydroponics. This method enables plant cultivation in controlled environments, yet manual monitoring of key parameters—such as water temperature, pH, and water level—is often inefficient and error-prone. This study presents the development of an automated monitoring and control system based on the Internet of Things (IoT), utilizing a publish/subscribe architecture. The system is built using NodeMCU V3 and Arduino Uno, equipped with temperature, pH, and ultrasonic sensors, and implemented in a Deep Water Culture (DWC) setup. Testing results indicate that the system can accurately read environmental parameters and transmit data in real-time to Firebase, achieving a throughput of 7753 Bps, 0% packet loss, and an average delay of 0.197 seconds from NodeMCU to Firebase, and 2.226 seconds in the reverse direction. The heater, chiller, and water pump operate automatically based on predefined thresholds (±3°C for temperature and +2 cm for water level). All parameters can be remotely monitored and controlled via an Android application. The system has proven to be effective and efficient in supporting precision agriculture and offers a sustainable solution for optimizing hydroponic cultivation in limited land areas.